Peran Pengungkapan CSR dalam Memoderasi Pengaruh Penerapan Tax Planning dan IOS terhadap Nilai Perusahaan - Zulfa Rosharlianti (EkoPreneur, 2020)
This study aims to determine the impact of the implementation of tax planning, investment opportunity set on company value with disclosure of corporate social responsibility as a moderating variable. Data collection is carried out at the Indonesia Stock Exchange through the website www.idx.co.id. This type of research is quantitative research. The sampling technique in this study was purposive sampling, with criteria for manufacturing companies listed on the Indonesia Stock Exchange (BEI) for five years in a row namely 2015 - 2019, which produced 27 companies. The data analysis model used in moderated regression analysis (MRA). The results of this study indicate that the application of tax planning affects the value of the company, the investment opportunity set influences the value of the company, the disclosure of corporate social responsibility does not moderate the application of tax planning and the investment opportunity set on company’s value Keywords: application of tax planning; investment opportunity set; disclosure of corporate social responsiveness; the value of the company